Self-Reflection: A complex Connection among Language, Culture, Identity, and Difference - Berli Arta (English Education Department - Universitas Nasional Karangturi, 2023)
The identity-taking process involves a complicated push-and-pull relation from different related aspects like language, culture, and differences. To understand this concept deeper, a self-study is required to explore how one’s life experience of encountering diverse cultures, language barriers, and differences can trigger themselves to define who they are and what relation they have with their surroundings. This is study is a self-reflection based on the author’s personal life experience to ignite the challenges of constructing identity due to cultural barriers, language ownership, and social relations with other people involved.